High Dosage Diazepam as Single Antispasmodic Agent in the Treatment of Neonatal Tetanus - Sugitha N.; Suwendra P.; Sudaryat Suraatmaja (Indonesian Pediatric Society, 1983)
An evaluation of diazepam as a single antispasmodic drug in the treatment of neonatal tetanus was made on 30 neonates, who were admitted to the Dept. of Child Health, General Hospital, Denpasar. Diazepam (Valium) was given with the dose of 2,5 mg intravenously at 2 hours intervals. It can be increased in very severe cases, to a maximal dose of 40 mg/kgbw/day. The overall mortality of this study was 20%. Almost all deaths occurred within the first 5 days. Incubation period of less than 7 days, period of onset of less than 48 hours, age on admission of less than 5 days and spontaneous paroxysmal spasm were important factors to contribute to the high mortality. The mortality also rose in proportion to the severity according to Patel and Joag criteria.